2018
DOI: 10.1371/journal.pone.0193136
|View full text |Cite|
|
Sign up to set email alerts
|

High quality diet improves lipid metabolic profile and breeding performance in the blue-footed booby, a long-lived seabird

Abstract: Understanding the role of diet in the physiological condition of adults during reproduction and hence its effect on reproductive performance is fundamental to understand reproductive strategies in long-lived animals. In birds, little is known about the influence of the quality of food consumed at the beginning of the reproductive period and its short-term effects on reproductive performance. To assess the role of diet in the physiological condition of female blue-footed booby, Sula nebouxii (BFBO), during repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The more complex prey community, heterogeneous distribution, and different nutritional content of prey items in coastal habitats may thus promote foraging segregation, whereas oceanic areas, which have a less diverse and more ephemerally distributed prey community, may prevent this (Ashmole 1971). Indeed, booby species such as blue-footed boobies and brown boobies which have a more diverse diet (Mellink et al 2001;Ancona et al 2012;Castillo-Guerrero et al 2016;González-Medina et al 2018;Miller et al 2018) were more likely to exhibit sexual segregation in foraging (see Table 1). This contrasts to pelagic species such as red-footed boobies and masked boobies, which rely mostly on flying fish and squid (Schreiber and Hensley 1976;Young et al 2010a).…”
Section: Sex-specific Foraging Trip Parametersmentioning
confidence: 99%
“…The more complex prey community, heterogeneous distribution, and different nutritional content of prey items in coastal habitats may thus promote foraging segregation, whereas oceanic areas, which have a less diverse and more ephemerally distributed prey community, may prevent this (Ashmole 1971). Indeed, booby species such as blue-footed boobies and brown boobies which have a more diverse diet (Mellink et al 2001;Ancona et al 2012;Castillo-Guerrero et al 2016;González-Medina et al 2018;Miller et al 2018) were more likely to exhibit sexual segregation in foraging (see Table 1). This contrasts to pelagic species such as red-footed boobies and masked boobies, which rely mostly on flying fish and squid (Schreiber and Hensley 1976;Young et al 2010a).…”
Section: Sex-specific Foraging Trip Parametersmentioning
confidence: 99%
“…The flavonoid's capability to improve birds' lipid profile is due to the presence of Functional hydroxyl groups that mediate their antioxidant effects by scavenging free radicals and/or by chelating metal ions 29 . In addition, previous research also concluded that adding plant extracts to quails' diet showed significant improvement in the lipid profile, oxidative stress status, body weight, and egg-yolk cholesterol of quails under stress conditions 30,31 .…”
Section: Resultsmentioning
confidence: 96%
“…In BFBO females, the isotopic composition of whole blood has been found to be associated with variation in plasma triglyceride concentration, with females that feed at a higher trophic level (i.e. consuming a higher quality diet) showing higher triglyceride concentrations and higher reproductive performance than those that feed at lower levels [59]. Relationships between foot colour and the labile traits measured in our study are expected because, as we stated previously, foot colour is an honest signal of current nutritional condition, and diet and triglyceride concentration affect this condition.…”
Section: Discussion (A) Assortative Matingmentioning
confidence: 99%